Artocarpus heterophyllus (Jackfruit): An Overview - Prakash, Om; Kumar, Rajesh; Mishra, Anurag; Gupta, Rajiv (Pharmacognosy Reviews)
Artocarpus heterophyllus (Syn. Kathal) belonging to family Moraceae is an integral part of common Indian diet and is freely available in Indian and adjoining continents, its medicinal properties are also mentioned in Ayurveda. The plant is reported to possess antibacterial, anti-inflammatory, antidiabetic, antioxidant and immunomodulatory properties. Artocarpus heterophyllus is an important source of compounds like morin, dihydromorin, cynomacurin, artocarpin, isoartocarpin, cyloartocarpin, artocarpesin, oxydihydroartocarpesin, artocarpetin, norartocarpetin, cycloartinone, betulinic acid, artocarpanone and heterophylol which are useful in fever, boils, wounds, skin diseases, convulsions, diuretic, constipation, ophthalmic disorders and snake bite etc.
Keywords: Artocarpus heterophyllus; Moraceae; Phytochemistry; Pharmacological activities